2014
DOI: 10.1089/ars.2013.5515
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Antioxidant Enzymes and Their Impact on Neonatal Lung Disease

Abstract: Significance: Deficient antioxidant defenses and compromised ability to respond to oxidative stress burden the immature lung. Routine neonatal therapies can cause increased oxidative stress with subsequent injury to the premature lung. Novel therapeutic approaches to protect the premature lung are greatly needed. Recent Advances: Live cell imaging with targeted redox probes allows for the measurement of subcellular oxidative stress and for comparisons of oxidative stress across development. Comprehension of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 121 publications
(70 reference statements)
0
39
0
Order By: Relevance
“…The relationship of iNO to free radical production in human neonates is unclear. There is biological evidence that ROS are constitutively produced by cellular sources; however, when combined with O 2 , NO creates supra-physiologic levels of nitrogen dioxide (NO 2 ) and peroxynitrite (86). In acutely unwell neonates, reduction in ROS may offset NO 2 effects.…”
Section: Approach To Respiratory Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of iNO to free radical production in human neonates is unclear. There is biological evidence that ROS are constitutively produced by cellular sources; however, when combined with O 2 , NO creates supra-physiologic levels of nitrogen dioxide (NO 2 ) and peroxynitrite (86). In acutely unwell neonates, reduction in ROS may offset NO 2 effects.…”
Section: Approach To Respiratory Supportmentioning
confidence: 99%
“…In acutely unwell neonates, reduction in ROS may offset NO 2 effects. Excessive or prolonged exposure may cause cellular injury and compromise cell growth (86). Given the body of evidence advocating against the use of iNO routinely in the prevention of preterm morbidities, especially bronchopulmonary dysplasia (2), avoidance of exposure to iNO beyond the period required to reverse abnormal PVR and its consequences is recommended.…”
Section: Approach To Respiratory Supportmentioning
confidence: 99%
“…However, clinical trials and laboratory experiments using single antioxidants have shown them to be largely ineffective in ameliorating hyperoxia-induced lung injury [ 24 , 27 29 ]. Furthermore, an imbalance between different antioxidants can result in tissue damage [ 30 ], suggesting that supplementation with single antioxidants could be harmful. As antioxidant defense involves multiple pathways [ 30 ], supplementation with any single antioxidant is unlikely to provide adequate protection against injury caused by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Forces exerted by mechanical ventilation in supporting premature infants contribute to the oxidative stress. Berkelhamer and Farrow present a growing body of literature, suggesting that extrauterine oxidative stresses such as mechanical ventilation, hyperoxia, infection, and poor nutrition further impair the development of the AOE systems (1). This produces a feed-forward mechanism that propagates future oxidative injury when these systems have been compromised.…”
mentioning
confidence: 99%
“…This successful combined approach is one possible answer to the questions raised by the failure of antioxidant ''monotherapy'' to protect the neonatal lung in clinical application. Clinical trials that have tested single agents-for example, vitamin A, vitamin E, and SOD-have demonstrated only modest effects, if any, as reviewed by Berkelhamer and Farrow and by Dani and Poggi (1,4). Use of recombinant human superoxide dismutase 1 (rhSOD1) failed to prevent acute bronchopulmonary dysplasia (BPD) in preterm infants, but decreased the incidence of longer-term sequelae of prematurity: wheezing episodes, emergency room visits, and rehospitalizations in the first year of life.…”
mentioning
confidence: 99%